Cardiotoxicity of anti-cancer drugs: cellular mechanisms and clinical implications - Kwok, Cecilia; Nolan, Mark (Frontiers in Cardiovascular Medicine, 2023)
Cardio-oncology is an emerging field that seeks to improve quality of life and survival of many survivors of cancer. It is pertinent for clinicians to understand the cellular mechanisms of prescribed therapies, as improved clinician understanding contribute to more accurate communication with patients. Our aim is to review the cellular mechanisms of cardiotoxicity involved in commonly used anti-cancer treatments. We hope to identify gaps in literature and strategies to mitigate the effects of cardiotoxicity that could guide future research endeavours.